Management Strategies of the Modern Islamic Boarding School Assalaam Cooperative to Enhance Productive Economy in Supporting the Achievement of SDGs - Masfuroh Misfah; Rizka; Muthoifin (Profetika: Jurnal Studi Islam, 2024)
Objective: This research explores the management strategies of the Assalaam Islamic Boarding School Cooperative (Koppontren) in enhancing the productive economy and contributing to the achievement of Sustainable Development Goals (SDGs). The primary aim of this study is to analyze how the management system implemented by Koppontren Assalaam influences the development of productive economic activities within the context of an Islamic boarding school. Effective cooperative management is crucial to achieving the cooperative’s goals, which include fostering internal economic development and supporting the overall progress of the institution. The study is grounded in qualitative descriptive research, utilizing observation, interviews, and documentation for data collection. Theoretical framework: The theoretical framework is based on management principles, cooperative economics, and SDGs, particularly focusing on sustainable economic development. Literature Review: The literature review highlights key concepts such as the role of cooperatives in economic empowerment, the significance of strategic management in Islamic institutions, and the alignment of cooperative practices with the SDGs. Methods: The research identifies essential management aspects including market strategies, financing processes, human resource development, and the importance of efficient communication and organization within cooperative operations. Results: The findings of this study indicate that the Assalaam cooperative employs several key strategies for its productive economic development. These include market segmentation, strategic financing, human resource management, and clear functional roles. The cooperative has developed a network of relationships that promotes effective information exchange and communication, which enhances operational efficiency. Furthermore, the cooperative has introduced pilot business models to stimulate innovation and creativity, while also implementing a dynamic monitoring and evaluation system to ensure sustainable growth and continuous improvement. Implications: The implications of this research suggest that the management strategies of Koppontren Assalaam not only contribute to its economic sustainability but also align with the broader objectives of SDGs, particularly in terms of sustainable economic growth and community empowerment. Novelty: The novelty of this research lies in its focus on the integration of cooperative management practices with the SDGs framework, offering valuable insights for similar institutions.